1998
DOI: 10.1295/polymj.30.404
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Reactions of N-Phenylmaleimide and Mono- or Di-functional Allylphenols

Abstract: ABSTRACT:Thermal reactions of N-phenylmaleimide (PMI) and o-allylphenol (AP) or diallylbisphenol-A (DABA) were investigated using 13 C NMR and GPC in order to obtain information on the curing of bismaleimidodiphenylmethane (BMI) with DABA, widely used as thermosetting bismaleimide resins. In the thermal reactions of PMI and AP, I : I and 3: I adducts were generated through ene-reaction and sequential Diels-Alder reactions accompanying the polymer of PMI and AP. The products from PMI and DABA were the ene-adduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Regarding the reaction mechanism for DABA/BMIM, Enoki et al [23][24][25] and Reyx et al 26 reported that the thermal reaction of the monofunctional model compounds, 2-allylphenol and N-phenylmaleimide (PMI), produced the ene-adduct, which underwent the Diels-Alder reaction twice with two molars of PMI to form the 3:1 adduct ( Figure 5). In continued work, Shibahara et al 27 reported that the thermal reaction of DABA and PMI produced ene-adduct and chain-polymerized products, whereas the Diels-Alder adduct could not be detected. This difference in reactivity for 2-allylphenol/PMI and DABA/PMI was attributed to steric repulsion of DABA.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the reaction mechanism for DABA/BMIM, Enoki et al [23][24][25] and Reyx et al 26 reported that the thermal reaction of the monofunctional model compounds, 2-allylphenol and N-phenylmaleimide (PMI), produced the ene-adduct, which underwent the Diels-Alder reaction twice with two molars of PMI to form the 3:1 adduct ( Figure 5). In continued work, Shibahara et al 27 reported that the thermal reaction of DABA and PMI produced ene-adduct and chain-polymerized products, whereas the Diels-Alder adduct could not be detected. This difference in reactivity for 2-allylphenol/PMI and DABA/PMI was attributed to steric repulsion of DABA.…”
Section: Resultsmentioning
confidence: 99%
“…6 At first, comparison between the liquid and solid state 13 C NMR spectra was made. Figure 1 shows their spectra for a reaction mixture of PMI and AP (molar ratio 2/1) treated at 175°C…”
Section: Resultsmentioning
confidence: 99%
“…6 At first, comparison between the liquid and solid state 13 C NMR spectra was made. Figure 1 shows their spectra for a reaction mixture of PMI and AP (molar ratio 2/1) treated at 175°C for 2 h. Solid-state 13 C NMR spectra were obtained by CPMAS and spinning sideband interference was eliminated by TOSS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations